Factors Influencing Utilization of Maternal Health Services by Adolescent Young Mothers Aged 15-19 Years in Kiryandongo General Hospital - Isaac Ocheng V. O., Isaac; Ika, Eddy; Omona [PhD], Kizito (International Journal of Medicine, 2021)
Background: In Uganda, 25 % of adolescents age 15-19 have already begun childbearing, 19 % have already given birth and another 5 % pregnant with their first child. Utilization of maternal health services is, therefore, an effective approach to reducing the risk of maternal morbidity and mortality. Low utilization of Maternal Health Services (MHS) has been registered in many parts of Uganda.Objective: To identify the key factors that influenced the utilization of MHS by adolescent young mothers aged 15-19years in Kiryandongo general HospitalMethods: A Cross Sectional analytical design, both quantitative and qualitative was used. A total of 98 adolescent young mothers were randomly selected. Data was collected using semi-structure questionnaires and analyzed using SPSS version 19.Results: Level of utilization of MHS was 44.9%. The socio-demographic (personal) factors that significantly influenced MHS utilization were; maternal age (COR= 0.29; 95% CI: 0.13-0.67, p = 0.003), husband’s education level (COR= 0.19; 95% CI: 0.08-0.47, p =0.000) and husband’s monthly income (COR= 0.35; 95% CI: 0.15-0.80, p = 0.012). Health System factors that influenced MHS utilization included; Time for travelling to reach health facility (COR=2.39; 95% CI: 1.03-5.52, p = 0.040) and Cost of the health services (COR= 2.68; 95% CI: 1.17-6.15, p =0.019).Conclusion: Strategies in addressing decision-making norms, engaging in massive community dialogue and designing appropriate communication strategies may help improve MHS utilization.